Outdoor site and facility management tools for creating memorable places - Whyman, Wynne 1961- (Human Kinetics, 2008)
Tour site and facilities, whether a beautiful building, a welcoming camp setting, or a natural wilderness area, are a large part of what draws participants to your property. They are also your largest financial investment, so proper management of them is crucial. Outdoor Site and Facility Management: Tools for Creating Memorable Places is a comprehensive resource for staff, board members, management, and owners charged with the complex and challenging task of managing and maintaining properties. The book offers a step-by-step property management plan that will help you to provide the safe environment and positive atmosphere so important to creating memorable experiences for your participants. Rather than focus on the technical skills of facility maintenance or site development, this book offers a broad perspective of property management. It introduces an integrated systems approach to the management of a variety of organizations, such as overnight and day camps, conference centers, outdoor learning centers, government parks, dude and guest ranches, commercial camp grounds, schools, not-for-profit organizations, and religious organizations. You'll have creative strategies to manage day-to-day operations, such as these: Planning and forecasting; Board and administrator responsibilities; Working with volunteers; Natural resource management; Hiring staff; Budgeting and financial oversight; Time management; Record keeping; Risk management. You'll also find practical advice to help you make sound decisions and form solutions that are tailored to your unique property. The book spends a chapter on each of the key components of property management and includes 48 practical tools, such as forms and checklists; practical techniques and examples; sample job descriptions; a glossary; and a list of the indicators of successful management discussed in the chapter. With Outdoor Site and Facility Management: Tools for Creating Memorable Places, you'll gain a complete picture of your property's physical, ecological, financial, and personnel assets. Most important, you'll discover the best way to manage your property and ultimately increase the equity of your assets and the marketability and long-term viability of your operation